The identity of religion always comes up: the war, the mass media and the reproduction of Muslim identity in the west - Latif, Muhammad Asad (Social Network Analysis and Mining, 2024)
Islamophobia in the media occurs when media sources present hostile, inaccurate, and/or deceptive stories about Islam, Muslims, or Arabs. Islamophobia is the term used to describe strong antipathy or prejudice toward Muslims, intense hatred or fear of Islam, particularly as a political force, and the study of how and to what extent the media promotes There has been a lot of scholarly and political discourse on Islamophobia. The discourse around Islamophobia in the media often focuses on the rhetorical strategies utilized by individual media outlets or by the mass media of a given nation or region, such the US or Europe. A few instances of this are when Islam is portrayed in a poor light relative to other religions, when Muslims are linked to terrorism, when Muslims and their followers are portrayed as aggressive or primitive, and when Muslim viewpoints are excluded from discussions on politics and academia, among other subjects. On the other hand, reactions to talks about Islamophobia in the media frequently cast doubt on what actually qualifies as Islamophobia, how frequently, how severe, and how effective Islamophobic language is, as well as the political reasons for such talks. This study aims to determine whether or not there was obvious inherent bias by examining the tone, structure, and topics offered by the print media prior to a terrorist event. This study examines how the world press has connected Islam to terrorism and emphasizes how subliminal print messages might contribute to Muslim racial profiling and the spread of Islamophobia. The editorials of six prominent international newspapers between 2014 and 2017 provided the data for this study, which created strata of ten significant worldwide terrorism incidents at random. The investigator examined editorials for a month following the event. The researcher’s results and conclusions are obtained by statistical interpretation following data analysis using event methodology and content analysis.